Effect of catastrophic medical insurance on healthcare service utilization and quality - DING, Ruiqi (Institutional Knowledge at Singapore Management University, 2024)
China implemented catastrophic medical insurance (CMI) program to provide additional reimbursement for individuals requiring extensive healthcare services due to severe illnesses. This study empirically assesses the impact of the CMI program on the healthcare utilization and quality of care for severely ill patients, using medical insurance claim data from 2012 to 2018 in a capital city in China. The analysis yields the following conclusions: First, CMI decreased the medical expenditure of severe patients, but it had no impact on alleviating the financial burden. Second, CMI curbed abuse and saved medical resources, and in the meantime, it increased the use of expensive medicines in treatment. Third, CMI enhanced healthcare quality by lowering 30-day readmission rates. Fourth, increased utilization of expensive medicine helps explain the reduction in hospitalization readmissions. Lastly, the heterogeneity analysis reveals that CMI particularly benefited older individuals with severe illness to get better healthcare. However, it also intensified health inequalities favoring male and wealthy patients.